2017
DOI: 10.1097/mat.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Extracorporeal Life Support During Surgery for the Critical Airway Stenosis

Abstract: Anesthetic management of critical airway stenosis is often very challenging. Extracorporeal membrane oxygenation (ECMO) may provide adequate respiratory support when conventional approaches fail. We report our experience of ECMO support for critical airway surgery. Between April 2012 and March 2015, nine patients underwent ECMO-supported airway operation. The reason for surgery was tracheal stenosis in nine patients, and tracheomalacia, tracheal tumor, and external tracheal compression by mediastinal mass in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…3,11) First, the most useful indication of ECMO is airway obstructive disease. 7,[12][13][14] Most causes of death in patients with airway disease are respiratory failure due to airway obstruction. ECMO helps maintain life before surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…3,11) First, the most useful indication of ECMO is airway obstructive disease. 7,[12][13][14] Most causes of death in patients with airway disease are respiratory failure due to airway obstruction. ECMO helps maintain life before surgical correction.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO presents several advantages as an alternative in the anesthetic management of patients with a mediastinal mass. [ 3 ] The capability to provide both complete gas exchange as well as circulatory support makes it an ideal option for patients with a mediastinal mass effect on the airway and vascular structures. Furthermore, the fact that it can be placed under local anesthesia makes it convenient as it can be secured before induction of general anesthesia, as well as continued post-operatively if needed.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic management of patients with a mediastinal mass represents a challenge due to the potential for difficult ventilation and intubation, as well as the risk of cardiovascular collapse upon induction of general anesthesia. [ 1 2 ] Different anesthetic strategies and alternatives have been described,[ 3 ] each with its own risks and benefits. We present the case of a 70-year-old man who presented with a right para-tracheal mass extending into the anterior mediastinum with 90% mid-tracheal lumen obstruction who was successfully managed with venous-venous extra-corporeal membrane oxygenation (ECMO) during mass debulking and tracheal stent placement.…”
Section: Introductionmentioning
confidence: 99%
“…12) Venovenous ECMO was successfully used in four adult patients with post-intubation or post-tracheotomy tracheal stenosis during the airway surgery reported by Ahn et al 13) However, the cause of stenosis and the number of patients with PTTS were not specified. In 2017, Kim et al 14) reported nine patients underwent airway operation with the support of venovenous ECMO, of which only one traumatic patient with PTTS. The status quo is few reports further described the use of ECMO in such patient population.…”
Section: Discussionmentioning
confidence: 99%